Development of Cytoplasmic Male Sterile IR24 and IR64 Using CW-CMS/Rf17 System - Toriyama, Kinya (Rice (N Y), 2016)
BACKGROUND: A wild-abortive-type (WA) cytoplasmic male sterility (CMS) has been almost exclusively used for breeding three-line hybrid rice. Many indica cultivars are known to carry restorer genes for WA-CMS lines and cannot be used as maintainer lines. Especially elite indica cultivars IR24 and IR64 are known to be restorer lines for WA-CMS lines, and are used as male parents for hybrid seed production. If we develop CMS IR24 and CMS IR64, the combination of F(1) pairs in hybrid rice breeding programs will be greatly broadened. FINDINGS: For production of CMS lines and restorer lines of IR24 and IR64, we employed Chinese wild rice (CW)-type CMS/Restorer of fertility 17 (Rf17) system, in which fertility is restored by a single nuclear gene, Rf17. Successive backcrossing and marker-assisted selection of Rf17 succeeded to produce completely male sterile CMS lines and fully restored restorer lines of IR24 and IR64. CW-cytoplasm did not affect agronomic characteristics. CONCLUSIONS: Since IR64 is one of the most popular mega-varieties and used for breeding of many modern varieties, the CW-CMS line of IR64 will be useful for hybrid rice breeding. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12284-016-0097-2) contains supplementary material, which is available to authorized users.